The effects of auditory stimulation with music on heart rate variability in healthy women (Clinics, 2013)
OBJECTIVES: There are no data in the literature with regard to the acute effects of different styles of music on the geometric indices of heart rate variability. In this study, we evaluated the acute effects of relaxant baroque and excitatory heavy metal music on the geometric indices of heart rate variability in women. METHODS: We conducted this study in 21 healthy women ranging in age from 18 to 35 years. We excluded persons with previous experience with musical instruments and persons who had an affinity for the song styles. We evaluated two groups: Group 1 (n = 21), who were exposed to relaxant classical baroque musical and excitatory heavy metal auditory stimulation; and Group 2 (n = 19), who were exposed to both styles of music and white noise auditory stimulation. Using earphones, the volunteers were exposed to baroque or heavy metal music for five minutes. After the first music exposure to baroque or heavy metal music, they remained at rest for five minutes; subsequently, they were re-exposed to the opposite music (70-80 dB). A different group of women were exposed to the same music styles plus white noise auditory stimulation (90 dB). The sequence of the songs was randomized for each individual. We analyzed the following indices: triangular index, triangular interpolation of RR intervals and Poincaré plot (standard deviation of instantaneous beat-by-beat variability, standard deviation of the long-term RR interval, standard deviation of instantaneous beat-by-beat variability and standard deviation of the long-term RR interval ratio), low frequency, high frequency, low frequency/high frequency ratio, standard deviation of all the normal RR intervals, root-mean square of differences between the adjacent normal RR intervals and the percentage of adjacent RR intervals with a difference of duration greater than 50 ms. Heart rate variability was recorded at rest for 10 minutes. RESULTS: The triangular index and the standard deviation of the long-term RR interval indices were reduced during exposure to both music styles in the first group and tended to decrease in the second group whereas the white noise exposure decreased the high frequency index. We observed no changes regarding the triangular interpolation of RR intervals, standard deviation of instantaneous beat-by-beat variability and standard deviation of instantaneous beat-by-beat variability/standard deviation in the long-term RR interval ratio. CONCLUSION: We suggest that relaxant baroque and excitatory heavy metal music slightly decrease global heart rate variability because of the equivalent sound level.